Conceptions of Time in George Pachymeres and Nikephoros Gregoras - ÇELİK, SİREN (My University, 2022)
After a brief discussion of the notions of time in Late Byzantine history writing such as dating systems, chronology, perceptions of past and present, this paper will focus on the cases of George Pachymeres and Nikephoros Gregoras. How did the philosophical or ecclesiastical backgrounds of these historians influence their conceptions of time? The paper will discuss how Gregoras’ understanding of time fused philosophy, astronomy and history, whereas Pachymeres blended influences from the liturgy, the Old Testament and Aristotle. Thus, their conceptions of time essentially functioned as bridges between different disciplines and textual sources.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities